Geotechnical hazards from large earthquakes and heavy rainfalls - Hazarika, Hemanta; Kazama, Motoki; Lee, Wei F. (Springer, 2017)
This book is a collection of papers presented at the International Workshop on Geotechnical Natural Hazards held July 12-15, 2014, in Kitakyushu, Japan. The workshop was the sixth in the series of Japan-Taiwan Joint Workshops on Geotechnical Hazards from Large Earthquakes and Heavy Rainfalls, held under the auspices of the Asian Technical Committee No. 3 on Geotechnology for Natural Hazards of the International Society for Soil Mechanics and Geotechnical Engineering. It was co-organized by the Japanese Geotechnical Society and the Taiwanese Geotechnical Society. The contents of this book focus on geotechnical and natural hazard-related issues in Asia such as earthquakes, tsunami, rainfall-induced debris flows, slope failures, and landslides. The book contains the latest information and mitigation technology on earthquake- and rainfall-induced geotechnical natural hazards. By dissemination of the latest state-of-the-art research in the area, the information contained in this book will help researchers, designers, consultants, government officials, and academicians involved in the mitigation of natural hazards. The findings and other information provided here is expected to contribute toward the development of a new chapter in disaster prevention and mitigation of geotechnical structures.
Keywords: Soil mechanics.; Engineering geology.; Earthquakes.; Natural disasters.; elektronické knihy; electronic books